(3ShA GdeRGL GdeNJdas - (3LGdjfhSs
(3ChdgG (B:s
(3bGd LGdjfhS (B: (3Ef ShA GdeRGL GdeNJda QHeG cGf ai GdHOf cdg ef GdMjhGf `, cGdPi jYQV dg ef Pdc GdfhY ef GdESJSbGA GdeYQha HGddMei s
(3BNQgG (B:s
(3EdG Cf YdJg Jchf YfO Pdc CZdX Ke HYOg cJGHi ai MjdI GdHQA Je cJGH LGdjfhS ShA GdeRGM GdeNJda s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B120 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B290 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdhWfjI HeOQjO (B(3/5011) s
Keywords: (3GdWHs